Side-jump impulse correlates with speed skating sprint times - Allinger, T. L.; Smith, J. (1999)
Laboratory tests are used to evaluate the training status and potential performance of elite athletes. One test that may be useful for predicting speed skating performance is the side-jump. The side-jump is an explosive leg extension in the lateral direction, similar to the skating stroke and is used for off-ice training. The purpose of this study was to determine if the impulse generated during a side-jump correlated with skating performance. Sixteen members of the U.S. National Speedskating Team volunteered for testing (7 female, 9 male). Each athlete performed maximal effort side jumps from a force platform (AMTI, 1000 Hz), wearing running shoes. Three jumps from their left and right legs were recorded. Total impulse was calculated by numerical integration of the force-time components of the ground reaction force. The trials with the largest impulse (left and right legs) were averaged for each subject. These measurements were made one month after the skating season. The fastest skating time from the previous season ('98-'99) at World Cup and World Championship events was selected for each athlete at each distance they raced. The race distances included the 500, 1000, 1500, 3000 (female only), 5000, and 10,000m (male only). Race times were normalized for each distance to 500m (e.g., 1500m time / 3 = normalized 500m time). The sprint distances (500m, 1000m) were analyzed in a second group. Skaters (3 female, 1 male) with less than elite times in the 500m and 1000m distances were disqualified from the sprint data set (i.e., normalized times greater than 41s and 39s, women and men respectively). Because all-around World Cup races do not include a 1000m race, the five all-around skaters had only a 500m tme and the seven sprint skaters had both 500m and 1000m times in this data set. Two linear regressions were computed between total impulse and normalized times for (1) all the distances and (2) only the sprint distances. No significant correlation between the side-jump impulse and the normalized skating times existed when the data were examined over all the distances. For the sprint distances, the side-jump impulse showed a significant relation with the normalized race times (slope=-0.023, r=0.80, p<0.001, n=19), with larger impulses corresponding to faster skating times. Group values (mean±S.D.) for the normalized time and impulse were 38.11±0.85 s and 193.7±29.9 N-s, respectively. Based on these results, a maximal effort side-jump appears to reflect performance in a sprint race more closely than a distance race for elite speed skaters. Impulse measurements from a side-jump may be useful for evaluating training status and predicting skating performance for the sprint distances (500m and 1000m) in speed skating.